STYLISTIC DEVIATION IN THE SELECTED LITERARY WORKS OF KRISTIAN CORDERO - Mae N. Elamera, Erica; Arah O. Sales, Princess; B. Slleza, Kpecjoe (Universitas Muhammadiyah Lampung, 2023)
This study conducted a stylistic analysis focusing on the deviations in the five (5) Bikol poems of Kristian Cordero, an acclaimed poet, fiction writer, and filmmaker based in the Bicol region. The term stylistic deviation refers to violating the ordinary use of a language, language structure, and patterns. This aims to identify the distortions in language and discover the theme conveyed by the deviations. The depiction of deviations was done in three levels: lexical, semantic, and phonological. The five (5) poems from Cordero’s book